2017
DOI: 10.22616/erdev2017.16.n088
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic and catalystic enchancement of methane production from corn silage and grain residues

Abstract: Many biogas plants used corn silage and grain processing (dryers) residues as a raw material. Hydraulic retention time working with such raw materials is relatively long and requires large volumes of bioreactors. Variety of additives can be used to improve the anaerobic digestion process. This article shows the results of the study where the enzyme mixture and catalyst Metaferm are used for the digestion process echancement. Corn silage and grain processing residues were digested in 0.72 l bioreactors at tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…However, sawdust microorganisms decompose slowly and methane production is relatively low. As we have verified above [1,2], the separation of lignocellulolytic materials, straw, was enhanced by the addition of enzymes. The purpose of this study was to determine whether and to what extent the addition of enzymes improves methane production from a mixture of bird droppings and sawdust.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, sawdust microorganisms decompose slowly and methane production is relatively low. As we have verified above [1,2], the separation of lignocellulolytic materials, straw, was enhanced by the addition of enzymes. The purpose of this study was to determine whether and to what extent the addition of enzymes improves methane production from a mixture of bird droppings and sawdust.…”
Section: Introductionsupporting
confidence: 63%
“…Metaferm contains multi enzymes, microelements and B group vitamins as well growing stimulators. Our previous studies show that the use of catalyst Metaferm has a positive effect on methane yield in anaerobic fermentation process of some biomass" [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers reported that anaerobic fermentation of old bread resulted in specific biogas yield 650 l kg -1 VS , and specific methane yield 313 l•kg -1 VS [7]. In previous studies, the addition of catalyst Metaferm resulted in improvement of the methane yield from substrates with rather difficultly biodegradable corn silage and dried grains [8]. Therefore, this study will continue to explore an effect of the additive Metaferm on more easily fermentable biomass.…”
Section: Introductionmentioning
confidence: 81%
“…Total solid, ash and dry organic matter (DOM) contents of biomass were determined by known methods [12]. All substrates were carefully mixed together and filled in bioreactors before anaerobic fermentation (AF).…”
Section: Methodsmentioning
confidence: 99%